The Role of Collaboration and Peer Support in Predicting Teachers’ Readiness for Inclusion - Eden Y. Vitor; Lilibeth C. Pinili; Regina E. Sitoy; Reylan G. Capuno; Raymond C. Espina; Honorio C. Anora; Marjorie B. Añero (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study determined the role of collaboration and peer support in predicting teachers’ readiness for inclusive education at Ramon Duterte Memorial National High School, Cebu City Division, during the School Year 2025–2026. It specifically evaluated the level of collaboration, peer support, and teachers' preparedness for inclusion, while also investigating the correlations between collaboration and preparedness, as well as peer support and preparedness. The study utilized a descriptive–correlational quantitative research design and employed a complete enumeration sampling technique with eighty-five (85) teachers as respondents. The main tool for collecting data was a validated survey questionnaire. The statistical tools used were frequency count, percentage, weighted mean, standard deviation, and Pearson Product-Moment Correlation Coefficient. Findings revealed that the level of collaboration among teachers was very high, the level of peer support was very high, and the level of teachers’ readiness for inclusive education was high. Results further showed that there was a significant relationship between collaboration and teachers’ readiness for inclusive education, and a significant relationship between peer support and teachers’ readiness for inclusive education, with peer support emerging as the stronger predictor. Collaborating and receiving peer support have proved to make great contributions to teachers' preparedness for inclusive education. Finally, schools need to enhance structured collaborative practices, peer mentoring, and capacity-building programs in order to further augment the preparedness of teachers toward inclusive education.